2017
DOI: 10.1016/j.breast.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Social support and breast cancer: A comparatory study of breast cancer survivors, women with mental depression, women with hypertension and healthy female controls

Abstract: SS is a well-known determinant of wellbeing. Our study lends support to the spouse's or the partner's central role during the recovery phase of BC. Identification of factors improving the overall QoL of BC survivors is an important public health challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 42 publications
(41 reference statements)
3
22
0
5
Order By: Relevance
“…20 The spouse or partner, among the relatives, is responsible for offering 94.3% of social support in coping with the disease. 21 In the present study, it was observed the absence of family member/companion, throughout the therapeutic itinerary developed in another city, contributed to aggravate patient's insecurity, as verified in speeches by PM53RECTUM and PF49BREAST. Thus, the need for health professionals to use strategies to strengthen the family bond, in order to provide and facilitate the search for intra-family support, although it is difficult to experience the patient's fragility in the face of illness.…”
Section: Discussionsupporting
confidence: 57%
“…20 The spouse or partner, among the relatives, is responsible for offering 94.3% of social support in coping with the disease. 21 In the present study, it was observed the absence of family member/companion, throughout the therapeutic itinerary developed in another city, contributed to aggravate patient's insecurity, as verified in speeches by PM53RECTUM and PF49BREAST. Thus, the need for health professionals to use strategies to strengthen the family bond, in order to provide and facilitate the search for intra-family support, although it is difficult to experience the patient's fragility in the face of illness.…”
Section: Discussionsupporting
confidence: 57%
“…Al enfrentar el distrés psicológico, las mujeres casadas suelen recibir más apoyo emocional e instrumental durante el tratamiento (12,13) . Según Bloom et al (12) , el apoyo emocional está relacionado con un mayor bienestar mental, al igual que la autoestima.…”
Section: Introductionunclassified
“…Según Bloom et al (12) , el apoyo emocional está relacionado con un mayor bienestar mental, al igual que la autoestima. Por tanto, al incrementar el apoyo social se tienen efectos positivos en el funcionamiento biopsicosocial y en la calidad de vida; disminuyendo la probabilidad de padecer depresión (11,13) . Salakari et al (13) mencionan en su estudio que, las parejas eran identificadas como la mayor fuente de apoyo para afrontar la trayectoria del cáncer, mientras que el apoyo de otras personas cercanas no era tan relevante para las mujeres.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The social environment and social support from significant others is particularly important for cancer survivorship, as cancer survivors are often afraid of recurrence, face late effects of cancer treatment and chronic illnesses other than cancer that require lifestyle changes, and often encounter problems in their social lives (Jefford et al, 2017;Takahashi, 2016). Although family caregivers are primary support providers for cancer survivors (Crookes et al, 2016;Salakari et al, 2017), friends are important informal support resources for Japanese cancer survivors (Taniguchi & Wakasaki, 2016), so that it is important to maintain or improve relationships between cancer patients and their friends after disclosing cancer.…”
mentioning
confidence: 99%